1997
DOI: 10.1210/jcem.82.8.4145
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A as Serum Marker for Neuroendocrine Neoplasia: Comparison with Neuron-Specific Enolase and the α-Subunit of Glycoprotein Hormones

Abstract: Chromogranin A (CgA) is gaining acceptance as a serum marker of neuroendocrine tumors. Its specificity in differentiating between neuroendocrine and nonneuroendocrine tumors, its sensitivity to detect small tumors, and its clinical value, compared with other neuroendocrine markers, have not clearly been defined, however. The objectives of this study were to evaluate the clinical usefulness of CgA as neuroendocrine serum marker. Serum levels of CgA, neuron-specific enolase (NSE), and the alpha-subunit of glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
3
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 31 publications
4
55
3
5
Order By: Relevance
“…The specificity of CgA in this study is therefore in the same range as that previously reported using the same immunoassay (Baudin et al, 1998). None of the classic false positive CgA results were found in these patients (O'Connor et al, 1989; Takiyyudin et al, 1990;Cryer et al, 1991;Deftos, 1991; Takiyyudin et al, 1991;Nobels et al, 1997;Sanduleanu et al, 1999). Above all associated NET as part of multiple endocrine neoplasia were excluded.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The specificity of CgA in this study is therefore in the same range as that previously reported using the same immunoassay (Baudin et al, 1998). None of the classic false positive CgA results were found in these patients (O'Connor et al, 1989; Takiyyudin et al, 1990;Cryer et al, 1991;Deftos, 1991; Takiyyudin et al, 1991;Nobels et al, 1997;Sanduleanu et al, 1999). Above all associated NET as part of multiple endocrine neoplasia were excluded.…”
Section: Discussionsupporting
confidence: 82%
“…Given its low sensitivity in MTC patients, CgA does not appear to be capable of competing with CT for the diagnosis of MTC. This CgA sensitivity was in the lower range of values described in previous studies (O'Connor and Deftos, 1986;Blind et al, 1992;Nobels et al, 1997). Such discrepancies may partly be explained by different biological assays used to measure CgA.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…From other authors observations the sensitivity of CgA as a marker of neuroendocrine tumors of the gastrointestinal tract varies between 10-100% with specificity of 68-100% [17,20]. Values of CgA diagnostic sensitivity and specificity available in the literature differ depending on the secretory activity and the degree of tumor and also depend on the method used to determine the concentration of CgA and accepted cut-off value [5,6,10,17,25,32].…”
Section: Discussionmentioning
confidence: 96%
“…In every case of diagnosed NET determination of CgA concentration has a significant impact on the prognosis and the choice of treatment and clinical outcome. Prognosis for the patients with NET secreting CgA is better, having a longer survival time and a prolonged time to progression [5,10,18,22,24,25].…”
Section: Introductionmentioning
confidence: 99%